Effect of Several Flowering Plants on Diversity and Populations of Pests and Natural Enemies in Cayenne Pepper (Capsicum frutescens)â€: Pengaruh Beberapa Tanaman Berbunga terhadap Keragaman dan Populasi Hama serta Musuh Alami pada Pertanaman Cabai Rawit (Capsicum Frutescens) - Hidayah, Lailatul; Tri Haryadi, Nanang (Jurnal Online Pertanian Tropik, 2021)
ABSTRACT One of the causes of pest problems that dominate in cayenne pepper is the monoculture planting system. Monoculture cropping systems have a lower diversity of pests and natural enemies in the field compared to polycultures. imbalance in the ecosystem in a crop, causing insect pests to become more resistant and dominate. Utilizing flowering plants is one of the efforts to maintain the balance of the existing ecosystem in the cayenne pepper plantation. The purpose of this study was to determine the effect of flowering plant species on the population and diversity of pests and natural enemies of cayenne pepper, then find out what treatment is the most effective for reducing pest populations. This research was conducted from August to December 2021 on land located in Gebang Village, Southeastang District, Bondowoso. The research design used was a randomized block design (RAK) with several treatments including P0 (Control), P1 (Sesamum indicum), P2 (Sphagneticola trilobata), P3 (Turnera subulata) and P4 (Turnera ulmifolia). The observed variables were the population of pests and natural enemies, the diversity of pests and natural enemies. The results showed that several types of flowering plants had an influence on Arthropoda diversity in cayenne pepper plants with a moderate category, the population of pests and natural enemies showed significantly different results in several weeks. The most effective treatment that can reduce pests is P3 (Turnera subulata) treatment which can reduce the pest population of B. dorsalis and show the highest population of its natural enemy, Oxyopes.